Sexual Orientation and U.S. Military Personnel Policy An Update of RAND's 1993 Study - Defense Research Institute, National (RAND Corporation, 2010)
This study on sexual orientation and U.S. military policy, requested by the Senate Armed Services Committee and the Secretary of Defense in order to weigh repeal of the "Don't Ask, Don't Tell" policy, examines public and military opinion on allowing gay men and lesbians to serve without restriction; research on sexual orientation, unit cohesion, and recruiting and retention; and experiences of domestic agencies and foreign militaries.